The Role of Xanthine Oxidase in Hemodialysis-Induced Oxidative Injury: Relationship with Nutritional Status - Miric, Dijana (Hindawi Publishing Corporation, 2013)
The role of xanthine oxidase (XOD) in patients undergoing chronic hemodialysis treatment (HD) is poorly understood. Geriatric nutritional risk index (GNRI) ≤ 90 could be linked with malnutrition-inflammation complex syndrome. This study measured XOD, myeloperoxidase (MPO), superoxide dismutase (SOD), lipid hydroperoxides, total free thiol groups, and advanced oxidation protein products (AOPP) in 50 HD patients before commencing (pre-HD) and immediately after completion of HD session (post-HD) and in 22 healthy controls. Pre-HD serum hydroperoxides, AOPP, XOD, and SOD were higher and total thiol groups were lower in patients than in controls (P < 0.05, resp.). Compared to baseline values, serum MPO activity was increased irrespective of GNRI status. Serum XOD activity was increasing during HD treatment in the group with GNRI ≤ 90 (P = 0.030) whilst decreasing in the group with GNRI > 90 (P = 0.002). In a multiple regression analysis, post-HD serum XOD activity was independently associated with GNRI ≤ 90 (β  ± SE: 0.398 ± 0.151; P = 0.012) and HD vintage (β  ± SE: −0.349 ± 0.139; P = 0.016). These results indicate that an upregulated XOD may be implicated in HD-induced oxidative injury contributing to accelerated protein damage in patients with GNRI ≤ 90.